Assessment of available phyllochinon in the leaves of Berberis thunbergii DC - Smoilovska, H.P. (Lublin Science and Technology Park S.A., 2017)
Family Berberidaceae contains approximately 15 genera and 650 species. Specimen of this family is grown up practically in all continents but mostly they occur in temperate and subtropical areas in the northern hemispher.Berberis fruit, bark, leaves, roots are used in folk medicine. Medicinal teas based on Berberis tonic organism, increase blood coagulation, intensify bile secretion, cause angiostenosis and uterus contractilit.Phyllochinone amount in the leaves Berberis thunbergii DC, species “Atropurpureanana” has been investigated by spectrophotometry. Maximum concentration for vitamin K has been observed during flowering and at once after it. It is 5.59%.
Keywords: phyllochinon; berberis thunbergii